Robert B. Parker's Big shot - Parker, Robert B., 1932-2010; Farnsworth, Christopher (Parker, Robert B., 1932-2010. Jesse Stone novels., 2026)
"Police Chief Jesse Stone finds himself in the crosshairs of a rich hedge fund manager dead set on making Paradise Jesse's personal hell, in this latest installment of Robert B. Parker's beloved series. Fresh off an acquittal in a multibillion-dollar fraud case, Ramsey Devlin doesn't think the law applies to him. This becomes apparent when Jesse finds him passed out, drunk, and on the side of the road in a McLaren worth more than most people's homes. After Devlin takes a swing at him and Jesse swiftly dumps him in the drunk tank, Jesse realizes he's made an enemy. Devlin makes it his life's mission to use his money and influence to provoke Jesse. And thanks to a few big campaign donations, he's got Jesse's nemesis, Gary Armistead, the mayor of Paradise, on his side. Devlin's even got Molly Crane, Jesse's deputy chief, wanting to act on her violent urges. Jesse has every reason to want Devlin out of his town. But when he vanishes, and bloodstains are found on the carpet of his monstrous seaside mansion, Jesse finds himself the main suspect in Devlin's disappearance. Suspended from his position as chief, Jesse must solve the case and prove his own innocence-or he might be the one to wind up behind bars"-- Provided by publisher.